The protection of intellectual property in international law - Grosse Ruse-Khan, Henning, 1974- (Oxford : Oxford University Press, 2017)
This volume examines intellectual property (IP) protection in the broader context of international law. Against the background of the debate about norm relations within and between different rule systems in international law, it construes a holistic view of international IP law as an integral part of the international legal system.
This edition previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on July 20, 2017).
Keywords: Intellectual property; Intellectual property (International law); Law; Laws of specific jurisdictions & specific areas of law